Concentration of fusel oil in alcohol column - Osipenko, Olexiy; Dolomakin, Yuriy; Osypenko, V. (My University, 2013)
To improve the process of removal of fusel oils in food distillation of ethyl alcohol is advisable to identify the areas of concentration in the system ethanol-water-izoamilol that at rectification form condensates heterogeneous type, and identify some of their technological characteristics.
Keywords: алкоголь; колона; сивушне масло; сивушное масло; alcohol; column; fusel oil; кафедра машин і апаратів харчових та фармацевтичних виробництв